You ya de SciPy : Python ke xue yan jiu de mei xue = Elegant SciPy : the art of scientific Python - Nunez-Iglesias, Juan; Van der Walt, Stéfan; Dashnow, Harriet (GoTop Information, Inc., 2018)
Detailed summary in vernacular field.